GERMINAÇÃO E VIGOR DE SEMENTES DE Enterolobium contortisiliquum (VELL.) MORONG. ARMAZENADAS Orientadora: Profa. Dra. Edna Ursulino Alves AREIA - PB 2013 - Silva, Rosemere dos Santos (2013)
The species Enterolobium contortisiliquum (Vell.) Morong., commonly known as tambor is a Fabacea of wide occurrence, used in the recovery of degraded areas; the study of seed storage is a strategy that avoids losses both in terms of quality and quantity. Thus the aim of this study was to evaluate the physiological quality of seeds of E. contortisiliquum (Vell.) Morong. stored in different packaging, environments and storage periods. Seeds were obtained from ripe fruits at the beginning of dispersal in seven mother trees located in Areia, PB, between the months of november and december of 2010 and then taken without the Seed Analysis Laboratory, Department of Plant and Environmental Sciences Center of Agricultural Sciences of the Federal University of Paraíba, following a completely randomized design in a split-plot, with the major portion consisting of the environments (laboratory freezer, freezer and refrigerator), the subplot for packaging (kraft paper, cloth, aluminum plastic (PP) and PET bottle) and constituted by subsubplot storage periods (0, 30, 60, 90, 120, 150, 180, 210, 240 and 270 days). To evaluate the physiological quality was determined the water content, percentage, first count and the speed of emergency as well as the length and dry weight of shoots and roots. The seeds of E. contortisiliquum, can be packed in plastic bag of polypropylene (PP) and stored for 270 days without considerable reduction in vigor.